2007
DOI: 10.4209/aaqr.2007.05.0028
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Activation Analysis of Atmospheric Aerosols from a Small Pacific Island Country: A Case of Suva, Fiji Islands

Abstract: A systematic study was developed to investigate the quality of air in Suva, the capital city of Fiji Islands. This is the first work of its kind in the South Pacific Islands and was aimed at characterizing the elemental abundances in total suspended particulate (TSP) matter in Suva's air.Aerosol samples were collected from 11 locations in Suva during the period 2000-2003 using a high-volume sampler. Concentrations of some heavy metals and other trace elements in these atmospheric aerosols were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This was clearly expected due to the nature of the factory itself. In comparison, similar work conducted by the authors in the ambient environment of Suva could only characterise 3-5 % of the total aerosols elementally (Garimella & Deo, 2007).…”
Section: Elemental Abundances In the Aerosolsmentioning
confidence: 98%
See 2 more Smart Citations
“…This was clearly expected due to the nature of the factory itself. In comparison, similar work conducted by the authors in the ambient environment of Suva could only characterise 3-5 % of the total aerosols elementally (Garimella & Deo, 2007).…”
Section: Elemental Abundances In the Aerosolsmentioning
confidence: 98%
“…This certainly reveals that a great deal of anthropogenic aerosols is generated inside the factory. Garimella & Deo (2007) have shown that the measured TSP levels in residential, traffic, and industrial areas of Suva are in the range 9-43, 20-50, and 33-91 µg m -3 respectively. The levels of TSP measured outside the factory and in the ambient environment conform to their levels stated for industrial areas.…”
Section: Observations From High Volume Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence-induced resuspension of fine particles from surfaces is closely related to a variety of applications and phenomena, such as cleaning and preparation of semiconductor surfaces (Lim et al, 2005), dose supply control of dry powder inhaler (Farkas et al, 2015), transport of microorganisms in environments (Jamieson et al, 2005), and spread of radioactive dust related to the operation of a nuclear reactor (Garimella and Deo, 2007). Recently, particle resuspension has gained increasing attention because deposited particles could be an important source for indoor and outdoor airborne particulate matters (PM) and has the potential to prolong human exposure to harmful particles (Munir et al, 2013;You et al, 2013;You and Wan, 2014c;Dimitriou, 2015).…”
Section: Introductionmentioning
confidence: 99%